Hubungan Kepemimpinan Kepala Madrasah Dan Motivasi Guru Dengan Disiplin Kerja Guru MTS Negeri Saradan Kabupaten Madiun - Anas Syahrur Munir; Adibah Jauhari (FAI- Undar, 2021)
Teacher have a very important roleand functionto form students morality and mentality. To reach goal of educationin schoolinflunced byteachers behaviour in profession. This reality that make teachers had to have a high diciplinfor doing their function, because teacher is the figure that guide students and their surroundings The purpose of this research is to analysis correlation leadership, work motivation and diciplin among teachers in Islamic Yunior State School of Saradan Madiun. The population and sample in this research is all the teachers in Islamic Yunior State School of Saradan Madiun which is 17 teachers, because the population is less than 100 in its account, then the sample is taken from that population. Design ofthis research isquantitative research because testing relationship between threevariable there is Leadership, Work Motivation and Diciplin. Collecting data methods using questionnaire which is given to all the teachers inIslamic Yunior State School of Saradan Madiunas the respondents than it is analyzed using pearson correlation and proceed with 17th version of SPSS software. The results of this study indicate that: (1) there is a positive significant (p = 0,00) the correlation leadership on work motivation among teachers in Islamic Yunior State School of Saradan Madiun with coefficient correlation amounted 0,840 (2) positive significant (p = 0,00)correlation work motivation on diciplin among teachers in Islamic Yunior State School of Saradan Madiunwith coefficient correlation amounted 0,810 (3)positive significant (p = 0,00) simultanly correlation leadership and work motivation on diciplin among teachers in Islamic Yunior State School of Saradan Madiunwith contributing amounted 75,2%. Based on these results, the authors give advice to all teachers in Islamic Yunior State School of Saradan Madiun as much as possible in order to show the motivation and discipline in the discharge of duty as teachers to provide role models for the students and for the school community